2021
DOI: 10.1016/j.heliyon.2021.e07348
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ambient temperature on blood pressure of patients undergoing hemodialysis in the Pantanal-Brazil

Abstract: The objective was to analyze the association of changes in pre-dialysis systolic and diastolic blood pressure with air temperature in a municipality in the Brazilian Pantanal, a tropical climate area. Longitudinal panel study, with analysis of mixed effects models of 133 hemodialysis patients in the city of Cáceres-Mato Grosso in 2014. Air temperature showed an inverse association with pre-dialysis systolic and diastolic blood pressure. With each increase of 1 °C in the mean air temperature, the pre-dialysis s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
(87 reference statements)
1
3
0
Order By: Relevance
“…Air temperature, especially cold temperature, has a short-term effect on blood pressure (Xu et al, 2019) because exposure to cold temperatures can increase activation and vasoconstriction of the sympathetic nervous system, and reduce endothelial function, which can lead to increased blood pressure (Park et al, 2020). The results of this study are in line with the findings showing that the percentage of patients with large-artery atherosclerosis (LAA) in the low-temperature group was significantly greater than that in the non-low-temperature group (p<0.05) because low temperatures can cause an increase in platelets and red blood cells, as well as increase blood viscosity, adhesion and platelet activation, all of which can lead to thrombosis (Chen et al, ), 2021Chen, Shang, et al, 2019;Halil Gibran & Heriyani, 2020;Hartwig et al, 2021;Jayarajah & Seneviratne, 2019;Karim et al, 2021;Polcaro-Pichet et al, 2019;Tochihara et al, 2021;Toffoli et al, 2023;Umishio et al, 2019;Wu et al, 2021a).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Air temperature, especially cold temperature, has a short-term effect on blood pressure (Xu et al, 2019) because exposure to cold temperatures can increase activation and vasoconstriction of the sympathetic nervous system, and reduce endothelial function, which can lead to increased blood pressure (Park et al, 2020). The results of this study are in line with the findings showing that the percentage of patients with large-artery atherosclerosis (LAA) in the low-temperature group was significantly greater than that in the non-low-temperature group (p<0.05) because low temperatures can cause an increase in platelets and red blood cells, as well as increase blood viscosity, adhesion and platelet activation, all of which can lead to thrombosis (Chen et al, ), 2021Chen, Shang, et al, 2019;Halil Gibran & Heriyani, 2020;Hartwig et al, 2021;Jayarajah & Seneviratne, 2019;Karim et al, 2021;Polcaro-Pichet et al, 2019;Tochihara et al, 2021;Toffoli et al, 2023;Umishio et al, 2019;Wu et al, 2021a).…”
Section: Discussionsupporting
confidence: 88%
“…The diseases caused by exposure to air temperature mentioned above are related to the fact that the human body should be busy during the day and needs sleep at night to restore energy and heal. Some studies also explain that the temperature of the work environment, especially cold temperatures, can increase blood pressure (Chen et al, 2021;Chen, Shang, et al, 2019;Chen, Xue, et al, 2019;Halil Gibran & Heriyani, 2020;Hartwig et al, 2021;Jayarajah & Seneviratne, 2019;Karim et al, 2021;Park et al, 2020;Polcaro-Pichet et al, 2019;Tochihara et al, 2021;Toffoli et al, 2023;Umishio et al, 2019;Wu et al, 2021a). However, there are research findings from Grace et.al, (2017) which state that there is a significant relationship between exposure to cold air temperatures and changes in systolic and distolic blood pressure before and after work.…”
Section: Introductionmentioning
confidence: 99%
“…Cold temperatures are associated with high UF rates, which are a risk factor for SBP decline and thus more likely to meet the criteria of Fall40. In addition, cold temperatures are linked to higher pre-HD SBP [ 35 , 36 ], which may make individuals less likely to reach Nadir90/100 criteria, as the lowest intradialytic SBP determines it. Our results suggest that Fall40 is more sensitive to cold ambient temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies ( 16 , 17 ) have shown that intradialytic hypotension is associated with patient prognosis and is an independent risk factor for high hospitalization rates in MHD patients, as well as reduced survival; intradialytic hypertension is an independent risk factor for increased mortality in MHD patients. There are numerous studies on the mechanisms of combined hypertension on dialysis, while the main mechanism for the occurrence of blood pressure fluctuations during dialysis is not clear ( 18 ). Meanwhile, the smooth control of blood pressure during dialysis in MHD patients has great significance for improving the prognosis of dialysis patients and improving the quality of survival of dialysis patients.…”
Section: Discussionmentioning
confidence: 99%